2021
DOI: 10.1097/cm9.0000000000001446
|View full text |Cite
|
Sign up to set email alerts
|

Value of perfusion parameters and histogram analysis of triphasic computed tomography in pre-operative prediction of histological grade of hepatocellular carcinoma

Abstract: Background: Pre-operative non-invasive histological evaluation of hepatocellular carcinoma (HCC) remains a challenge. Tumor perfusion is significantly associated with the development and aggressiveness of HCC. The purpose of the study was to evaluate the clinical value of quantitative liver perfusion parameters and corresponding histogram parameters derived from traditional triphasic enhanced computed tomography (CT) scans in predicting histological grade of HCC. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…CTPI is a noninvasive technique that facilitates reproducible and quantitative assessments of perfusion parameters related to tumorassociated vascularization [8]. Radiometric imaging provides reliable quantitative perfusion data and excellent anatomical imaging ability and easily re ects microstructural changes at the functional level [3,5]. Recent perfusion studies on HCC have focused on this topic; however, very few studies on the surrounding liver parenchyma have been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTPI is a noninvasive technique that facilitates reproducible and quantitative assessments of perfusion parameters related to tumorassociated vascularization [8]. Radiometric imaging provides reliable quantitative perfusion data and excellent anatomical imaging ability and easily re ects microstructural changes at the functional level [3,5]. Recent perfusion studies on HCC have focused on this topic; however, very few studies on the surrounding liver parenchyma have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Kurucay M[4] used CTPI to evaluate liver cancer and reported that the HPI was signi cantly better than that obtained by MRI for diagnosing liver cancer. Shao CC [5] reported that quantitative hepatic perfusion parameters and corresponding histogram parameters can be used to predict the histological grade of HCC. Choi's liver perfusion imaging with cone-beam computed tomography (CBCT) provides supplementary information on tissue perfusion in TACE, which makes it easier to identify residual active lesions and effectively evaluate treatment response [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the fifth most frequently diagnosed cancer and the third cause of cancer-related mortality worldwide[ 1 , 2 ]. HCC accounts for 75%-90% of primary liver cancers and constitutes a major global health problem[ 3 ]; moreover, HCC is difficult to treat.…”
Section: Introductionmentioning
confidence: 99%